2014
DOI: 10.2337/db14-0558
|View full text |Cite
|
Sign up to set email alerts
|

GLP-1 Plays a Limited Role in Improved Glycemia Shortly After Roux-en-Y Gastric Bypass: A Comparison With Intensive Lifestyle Modification

Abstract: Rapid glycemic improvements following Roux-en-Y gastric bypass (RYGB) are frequently attributed to the enhanced GLP-1 response, but causality remains unclear. To determine the role of GLP-1 in improved glucose tolerance after surgery, we compared glucose and hormonal responses to a liquid meal test in 20 obese participants with type 2 diabetes mellitus who underwent RYGB or nonsurgical intensive lifestyle modification (ILM) (n = 10 per group) before and after equivalent short-term weight reduction. The GLP-1 r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
75
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(85 citation statements)
references
References 46 publications
8
75
2
Order By: Relevance
“…Here, we demonstrate that blockade of peripheral GLP-1R signaling partially reverses the improvement in oral glucose tolerance induced by RYGB, a result supported by studies performed in rats and human patients (4,9,26,32). In contrast, however, we found that neither peripheral nor central GLP-1R signaling is required for the weight loss observed after RYGB.…”
Section: Discussionmentioning
confidence: 30%
“…Here, we demonstrate that blockade of peripheral GLP-1R signaling partially reverses the improvement in oral glucose tolerance induced by RYGB, a result supported by studies performed in rats and human patients (4,9,26,32). In contrast, however, we found that neither peripheral nor central GLP-1R signaling is required for the weight loss observed after RYGB.…”
Section: Discussionmentioning
confidence: 30%
“…It has further been shown that patients who achieve similar weight loss after gastric banding, a procedure which does not affect the incretin response, and RYGB exhibit similarly improved insulin sensitivity and β cell function [21]. GLP-1 receptor antagonism has also been reported to not fully reverse the favourable effects on glycaemic control after RYGB in T2DM patients [22]. In fact, in the long term, weight loss maintenance has been identified as a critical factor for T2DM control after RYGB [23,24].…”
Section: Introductionmentioning
confidence: 96%
“…in the IGT and NGT groups, and clearly demonstrated in studies using pharmacological blockade of the GLP-1 receptor (29,30,51,54). It could be argued that the increased postprandial GLP-1 levels during the days preceding the IVGTT could in part explain the enhanced first-phase ISR and AIRg after RYGB, since pharmacological administration of GLP-1 or GLP-1 agonists have been shown to restore both first-and second-phase insulin secretion to iv glucose in patients with type 2 diabetes (17).…”
Section: E540 ␤-Cell Function and Glucose Effectiveness After Rygbmentioning
confidence: 99%
“…Increased glucagon-like peptide-1 (GLP-1) contributes importantly to increased postprandial insulin secretion after RYGB, as demonstrated in studies using pharmacological blockade of the GLP-1 receptor (29,30,51,54).…”
mentioning
confidence: 99%